Mental Health Communication: The Phenomenon of Cyber Sexual Harassment Through Social Media - Hero, Eko; Astini, Bunga (Department of Communications, Universitas Islam Indonesia, 2023)
Sexual harassment via social media may cause some negative impacts, including depression, self-isolation, and even suicide, especially among victims whose pictures or videos are then uploaded by the perpetrators. Applying qualitative literature review, this research aims to conceptually explore problems regarding cyber sexual harassment through social media. The research shows that in Indonesia public should give more serious attention to the issue of cyber ​​sexual harassment. Nowadays, public still lack of proper knowledge to classify things that fall into cyber ​​sexual harassment category. Sexual harassment as a form of immoral action against someone involving aspects of pornographic acts may cause psychological conditions that disrupt mental harmony.